y=sin(x+y)的隐函数的二阶导数.

来源:学生作业帮助网 编辑:作业帮 时间:2024/08/02 15:39:37
y=sin(x+y)的隐函数的二阶导数.
x)-ӨЮ|> O>~mOrlU_`gC0ű`JVPR]39̷10&L/a BeFC`&MPG2-CVb3Au+Q%a 5<Em6v֢M3{~qAb4mт8 g@>B8,uavCMC K- tp݊ :5eCs {znG"Kk$

y=sin(x+y)的隐函数的二阶导数.
y=sin(x+y)的隐函数的二阶导数.

y=sin(x+y)的隐函数的二阶导数.
y'=[sin(x+y)]'(x+y)'=(1+y')cos(x+y)=cos(x+y)+y'cos(x+y)
y'=cos(x+y)/[(1-cos(x+y)]
y''=[cos(x+y]'(x+y)'+y''cos(x+y)+y'[cos(x+y)]'
=-(1+y')sin(x+y)+y''cos(x+y)-y'(1+y')sin(x+y)
y''[cos(x+y)-1]=(1+y')^2sin(x+y)
={1+cos(x+y)/[(1-cos(x+y)]}^2sin(x+y)
=sin(x+y)/[cos(x+y)-1]^2
y''=sin(x+y)/[cos(x+y)-1]^3

y'=cos(x+y)*(1+y')=cos(x+y)+y'cos(x+y)
∴y'=cos(x+y)/[(1-cos(x+y)]
y''=-sin(x+y)*(1+y')+y''cos(x+y)+y'*(-sin(x+y)*(1+y'))
∴[cos(x+y)-1]y''=sin(x+y)*(1+y')²,即y''=sin(x+y)/[cos(x+y)-1]³